Sex and sensibility : stories of a lesbian generation - Stein, Arlene (University of California Press, 1997)
In the first book to analyze shifts in lesbian identity, consciousness, and culture from the 1970s to the 1990s, Arlene Stein contributes an important chapter to the study of the women's movement and offers a revealing portrait of the exchange between a radical generation of feminists and its successors. Tracing the evolution of the lesbian movement from the bar scene to the growth of alternative families, Stein illustrates how a generation of women transforme.